Apakah asing memberikan nilai tambah pada industri keuangan di Indonesia? - Leonita, Lily (Universitas Tarumanagara, 2017)
The paper aims to study the value created by foreign shareholders in Indonesian banking over the period 2011-2016. We analyzed the value creation by foreign shareholders by comparing the key financial performance. We analyzed 7 micro key financial ratios (profitability, efficiency, growth, firm size, liquidity, solvency, and asset quality). We used parametric panel data dummy regression. The empirical results show that banking owned by foreign shareholders gave value to profit margin and growth of revenue and assets. The research also found that foreign shareholders were better at managing liquidity ratios such as loan-to-deposit.